HUBUNGAN TIPE POLA ASUH ORANG TUA DENGAN PERKEMBANGAN PSIKOSOSIAL ANAK USIA PRASEKOLAH DI TK PERTIWI 1 DESAPURBOWANGI KECAMATANBUAYAN KABUPATEN KEBUMEN - Wuri Utami; N Nurlaila; Riska Qistiana (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Preschool children, 3–6 years old, are problematic or difficult age.  This period usually has behavior problem resulting from the unique personality process and having freedom demanding. Their psychosocial development is between initiative stage versus guilty one. Parents’ parenting is the ability of parents to provide time, attention, and support in order their children can grow and develop very well.The aim of this study is to determine correlation between the type of parents’ parenting and psychosocial development of preschool children at Pertiwi I Kinder Garten, Purbowangi, Buayan, Kebumen.The present study was correlation research with cross sectional approach.The samples were 70 parents and their children taken by saturated sampling technique. Data were collected by using questionnaires. Statistical data analysis used Spearman Rank test.There were  50% respondents who applied democratic parenting type. Most children had good psychosocial development (62,9%). The result of the analysis showed by Spearman Rank p value (0.000).There were correlation between the type of parents’ parenting and psychosocial development of preschool children at Pertiwi I Kinder Garten, Purbowangi, Buayan, Kebumen. Keywords: Parenting, Psychosocial Development, Preschool Children